An expression atlas of human primary cells: inference of gene function from coexpression networks - Mabbott, Neil A; Baillie, J Kenneth; Brown, Helen; Freeman, Tom C; Hume, David A (BMC genomics, 2013)
Background The specialisation of mammalian cells in time and space requires genes associated with specific pathways and functions to be co-ordinately expressed. Here we have combined a large number of publically available microarray datasets derived from human primary cells and analysed large correlation graphs of these data. Results Using the network analysis tool BioLayout Express 3D we identify robust co-associations of genes expressed in a wide variety of cell lineages. We discuss the biological significance of a number of these associations, in particular the coexpression of key transcription factors with the genes that they are likely to control. Conclusions We consider the regulation of genes in human primary cells and specifically in the human mononuclear phagocyte system. Of particular note is the fact that these data do not support the identity of putative markers of antigen-presenting dendritic cells, nor classification of M1 and M2 activation states, a current subject of debate within immunological field. We have provided this data resource on the BioGPS web site ( http://biogps.org/dataset/2429/primary-cell-atlas/ ) and on macrophages.com ( http://www.macrophages.com/hu-cell-atlas ).